2014
DOI: 10.4321/s1889-836x2014000500002
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencia de vitamina D en España: ¿realidad o mito?

Abstract: Vitamin D 3 (colecalciferol) is formed from its precursor 7-dehydrocholesterol in the skin by ultraviolet irradiation. In the liver the vitamin D 3 is hydroxylated to form 25-hydroxyvitamin D 3 , which is metabolised to its active metabolite 1,25-dihydroxyvitamin D 3 preferentially in the kidney. Vitamin D 3 may also be provided in the diet, which is a significant source of supply only in the case of insufficient exposure to sunlight. Blue fish naturally contains large quantities of vitamin D 3 , while other f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 76 publications
2
6
0
3
Order By: Relevance
“…In this study, we found a high prevalence (89.9%) of deficient or insufficient serum levels of vitamin D (serum 25(OH)D3, <30 ng/mL) in a group of 273 elderly subjects, representative of a healthy age-related Spanish population. Our results are similar to previous studies in Spanish populations [19,20,21,22].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found a high prevalence (89.9%) of deficient or insufficient serum levels of vitamin D (serum 25(OH)D3, <30 ng/mL) in a group of 273 elderly subjects, representative of a healthy age-related Spanish population. Our results are similar to previous studies in Spanish populations [19,20,21,22].…”
Section: Discussionsupporting
confidence: 93%
“…Mean serum 25(OH) concentration in our study was similar to that reported in other European countries [18], similar to that detected in small studies carried out in different Spanish regions [8] and slightly lower than the concentration detected in larger Spanish studies, where the average levels fluctuated between 56 and 62 nmol/L [19][20][21]. The prevalence of vitamin D deficiency (<50nmol/L) in our study (55% in controls and 69% in BC cases) was higher than that reported among pre and post Mexican women (36%) [22], higher than the reported at European level (40%) [18], and also higher than that reported in other Spanish studies [19][20][21]23], but much [26,27], while the most recent reported a weak and nonsignificant inverse association [12].…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…behavior, use of UV protection cream and air pollution with ozone and nitrogen dioxide, which reduce suninduced vitamin D production [7,8].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Another factor to consider could be the level of vitamin D: in one meta-analysis, review authors observed an inverse association between vitamin D levels and the incidence of COPD exacerbations and a protective role for vitamin D supplements in patients with COPD and vitamin D deficiency [ 25 ]. In an earlier study, authors observed low levels of vitamin D in the female population of Spain [ 26 ]. Finally, numerous studies across different pathologies have found that women are at greater risk of not adhering to treatment, which could also have an impact on disease control [ 27 ].…”
Section: Discussionmentioning
confidence: 99%